Molecular basis for galactosylation of core fucose residues in invertebrates: identification of caenorhabditis elegans N-glycan core alpha1,6-fucoside beta1,4-galactosyltransferase GALT-1 as a member of a novel glycosyltransferase family. - Titz, A.; Butschi, A.; Henrissat, B.; Fan, Y.Y.; Hennet, T.; Razzazi-Fazeli, E.; Hengartner, M.O.; Wilson, I.B.; Künzler, M.; Aebi, M. (Journal of Biological Chemistry, 2009)
Galectin CGL2 from the ink cap mushroom Coprinopsis cinerea displays toxicity toward the model nematode Caenorhabditis elegans. A mutation in a putative glycosyltransferase-encoding gene resulted in a CGL2-resistant C. elegans strain characterized by N-glycans lacking the beta1,4-galactoside linked to the alpha1,6-linked core fucose. Expression of the corresponding GALT-1 protein in insect cells was used to demonstrate a manganese-dependent galactosyltransferase activity. In vitro, the GALT-1 enzyme showed strong selectivity for acceptors with alpha1,6-linked N-glycan core fucosides and required Golgi- dependent modifications on the oligosaccharide antennae for optimal synthesis of the Gal-beta1,4-fucose structure. Phylogenetic analysis of the GALT-1 protein sequence identified a novel glycosyltransferase family (GT92) with members widespread among eukarya but absent in mammals.